The Economics of Nation-Building: Methodological Toolkit and Policy Lessons - Dominic Rohner; Ekaterina Zhuravskaya (CESifo GmbH, 2024)
This article reviews the recent burgeoning political economics research on nation-building. We focus on three main aspects of this body of work. First, we discuss methodological issues related to measuring nation-building outcomes and provide a synthesis of studies that employ different techniques, such as surveys on identity, lab-in-the-field methods, and direct observation of actions signaling identity. Second, we explore preconditions for effective nation-building, particularly focusing on ethnolinguistic polarization and segregation, and discuss how these factors may influence policy choices and their effectiveness. We also consider geopolitical factors. Finally, we review advances in the literature evaluating the effects of major nation-building policies, including those that encourage inter-group contact, the choice of national education curriculum, propaganda, leadership, decentralization, and foreign interventions. We highlight instances when these policies work and when they backfire.
Keywords: D74; H11; H56; H77; N40; O10; Z10; P00; 330; nation-building; national identity; social cohesion; conflict